2010
DOI: 10.1161/circulationaha.109.924977
|View full text |Cite
|
Sign up to set email alerts
|

Red and Processed Meat Consumption and Risk of Incident Coronary Heart Disease, Stroke, and Diabetes Mellitus

Abstract: Background-Meat consumption is inconsistently associated with development of coronary heart disease (CHD), stroke, and diabetes mellitus, limiting quantitative recommendations for consumption levels. Effects of meat intake on these different outcomes, as well as of red versus processed meat, may also vary. Methods and Results-We performed a systematic review and meta-analysis of evidence for relationships of red (unprocessed), processed, and total meat consumption with incident CHD, stroke, and diabetes mellit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
779
6
38

Year Published

2010
2010
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 1,114 publications
(843 citation statements)
references
References 39 publications
20
779
6
38
Order By: Relevance
“…Egg consumption, including those used in cooking as well as baking, should be between two and four times per week. > Consumption of red meat (less than two servings, preferably lean cuts) and processed meats (less than one serving) should be small in both quantity and frequency as the intake of such meats has been consistently associated with some chronic diseases (cancers and CHD) (35,36) . > The combination of legumes (more than two servings) and cereals is a healthy plant protein and lipid source that should be considered as a meat alternative (37,38) .…”
Section: Federation Of European Societies Prevención Con Dieta Meditementioning
confidence: 99%
“…Egg consumption, including those used in cooking as well as baking, should be between two and four times per week. > Consumption of red meat (less than two servings, preferably lean cuts) and processed meats (less than one serving) should be small in both quantity and frequency as the intake of such meats has been consistently associated with some chronic diseases (cancers and CHD) (35,36) . > The combination of legumes (more than two servings) and cereals is a healthy plant protein and lipid source that should be considered as a meat alternative (37,38) .…”
Section: Federation Of European Societies Prevención Con Dieta Meditementioning
confidence: 99%
“…In relation to CVD, McAfee et al (2010) concluded that associations between red meat consumption and CVD risk are unclear as in many studies it is impossible to isolate the effects of red meat alone. However, the recent systematic review and meta-analysis of Micha et al (2010) identified that consumption of each serving of processed meats is associated with a 42% higher incidence of CHD (RR 1.42, 95% CI 1.07 to 1.89) and a 19% increase in type 2 diabetes (RR 1.19, 95% CI 1.11 to 1.27), but for red meat there was no association. There is clearly a need for more work in this area given the uncertainties over the definitions of red and processed meats and the need to understand the causative mechanisms for processed meats.…”
Section: Meat Consumption and Chronic Diseasementioning
confidence: 99%
“…Loss-adjusted food availability data from 2012 indicate that the average per capita consumption of red meat (processed and unprocessed) is 3·1 oz/d (88·5 g/d) or 53 % of the total meat intake; while NHANES 2011-2012 data indicate that the US consumption is 1·6 oz/capita per d (44·2 g/d) for unprocessed red meat (35 % of the total meat; data on total red meat are not available) and 1·0 oz/capita per d (27·8 g/d) for processed meat (red meat and poultry; 22 % of the total meat). Epidemiological studies have illuminated the increased health risks associated with red and processed meat consumption (2,3,(5)(6)(7)(8)(9)(10) , along with the decreased health risks associated with replacing red meat for equal servings of poultry, fish and plant-based foods (1,4,46) . With this preponderance of evidence, the 2015 Dietary Guidelines Advisory Committee most recently recommended reducing intake of red and processed meat in favour of plant-based alternatives in its scientific report released in February 2015 (23) .…”
Section: Data Comparisons To Dietary Recommendationsmentioning
confidence: 99%